Distrust As a Disease Avoidance Strategy: Individual Differences in Disgust Sensitivity Regulate Generalized Social Trust - Aarøe, Lene; Osmundsen, Mathias; Petersen, Michael Bang (Frontiers in Psychology, 2016)
Throughout human evolutionary history, cooperative contact with others has been fundamental for human survival. At the same time, social contact has been a source of threats. In this article, we focus on one particular viable threat, communicable disease, and investigate how motivations to avoid pathogens influence people's propensity to interact and cooperate with others, as measured by individual differences in generalized social trust. While extant studies on pathogen avoidance have argued that such motivations should prompt people to avoid interactions with outgroups specifically, we argue that these motivations should prompt people to avoid others more broadly. Empirically, we utilise two convenience samples and a large nationally representative sample of US citizens to demonstrate the existence of a robust and replicable effect of individual differences in pathogen disgust sensitivity on generalized social trust. We furthermore compare the effects of pathogen disgust sensitivity on generalised social trust and outgroup prejudice and explore whether generalised social trust to some extent constitutes a pathway between pathogen avoidance motivations and prejudice.